The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0100-204x2013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Stalk and sucrose yield in response to nitrogen fertilization of sugarcane under reduced tillage

Abstract: -The objective of this work was to evaluate the agroindustrial production of sugarcane (millable stalks and sucrose yield) after successive nitrogen fertilizations of plant cane and ratoons in a reduced tillage system. The experiment was carried out at Jaboticabal, SP, Brazil, on a Rhodic Eutrustox soil, during four consecutive crop cycles (March 2005 to July 2009). Plant cane treatments consisted of N-urea levels (control, 40, 80, and 120 kg ha -1 N + 120 kg ha -1 P 2 O 5 and K 2 O in furrow application). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 15 publications
2
26
1
6
Order By: Relevance
“…The fact that there was no effect of N application, especially in the plant cane cycle, was possibly due to the high content of organic matter in the soil used in the study (Table 1). The response of the plant cane to N is little expressive and normally occurs at low doses (Franco et al, 2010;Fortes et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that there was no effect of N application, especially in the plant cane cycle, was possibly due to the high content of organic matter in the soil used in the study (Table 1). The response of the plant cane to N is little expressive and normally occurs at low doses (Franco et al, 2010;Fortes et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen (N) fertilization can also promote yield increment in the plant cane cycle (Franco et al, 2010;Fortes et al, 2013); however, the responses to N application are still controversial. Localized irrigation, therefore, may present itself as an alternative, in which water and fertilizers are simultaneously applied through the drip system, promoting reduction in the consumption of water and fertilizers, which may result in higher sugarcane productions (Esperancini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…and lacking reports on S deficiency symptoms. Other studies, such as Prado and Pancelli (2008), Franco et al (2010), and Fortes et al (2013), using different types of N fertilizers, reported cane yield responses to N fertilization that fit to a quadratic function, but linear responses or the absence of response to N fertilization were also reported depending on locality and ratoon cycle. There is little biological basis to select a model over another to describe the crop response to N fertilization (Mead and Pike 1975).…”
Section: Nitrogen Use Efficiencymentioning
confidence: 97%
“…Nitrogen is usually a limiting nutrient to crop yield in the weathered tropical soils, and positive yield responses to N fertilization are observed for sugarcane in Brazil (Dourado Neto et al 2010;Fortes et al 2013), although less frequently to plant cane (first cycle) owing to higher contribution from N in soil and residue due to N mineralization, as well as the biological nitrogen fixation (Balasubramanian et al 2004;Urquiaga et al 2012;Otto et al 2016). A review on sugarcane pointed out the relatively low N use efficiency (NUE) by the crop, which averages 26% from a range of 7 to 40% of the N fertilizer applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation